Zakat management system with electronic mail / Muhammad Najmi Othman and Noorfaizalfarid Mohd Noor - Othman, Muhammad Najmi; Mohd Noor, Noorfaizalfarid (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The present financial industry is significantly impacted by technological advancements and inventions. Digital transformation is introducing new business models and transitioning from conventional to digital markets via the use of technology. The zakat system has become a significant component of the Islamic economy and financial system, and it must be digitised to be consistent with the modern digital era. This study intends to examine the administration of zakat applications at UITM and to identify the management areas that require rapid feedback between the applicant and ZAWAF. This study collects data from many sources, including books, journals, conference papers, and other relevant websites, using a qualitative research methodology. The majority of difficulties encountered by zakat applicants appear to be the result of obsolete system facilities. Applicants for zakat in the modern day frequently confront the issue of not knowing the status of their application. The majority of individuals today possess a mobile phone with internet access and an email account. Developing a Zakat management system with notepad plus, Visual Studio Code, and xampp. A system created for administrators, interviewers, and applicants that allows applicants to apply and check application status and also notifies applicants through email of the application status. While the administrator can oversee the applicant's application, the interviewer will conduct the interview. Planning, information collecting, design, development, testing, and documentation are included in the development process. The evaluation of a project involves the distribution of a questionnaire including usability test questions to thirty respondents. The test script is utilised for functional test execution. According to the test findings, the system is usable but requires further development.